2018
DOI: 10.1038/s41598-018-27442-w
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of Neotropical bats with hantavirus in Brazil

Abstract: Bats (Order: Chiroptera) harbor a high diversity of emerging pathogens presumably because their ability to fly and social behavior favor the maintenance, evolution, and dissemination of these pathogens. Until 2012, there was only one report of the presence of Hantavirus in bats. Historically, it was thought that these viruses were harbored primarily by rodent and insectivore small mammals. Recently, new species of hantaviruses have been identified in bats from Africa and Asia continents expanding the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
0
22
0
4
Order By: Relevance
“…Until the decade of 2000, Hantaviridae family was restricted to Rodentia, (Padula et al, ; Schmaljohn & Hjelle, ; Torres‐Pérez et al, ); however, since the early 2000s, recent discoveries found some hantavirus species in Indian shrews [order: Soricomorpha] (Klempa et al, ; Zhang, ) and American and European bats (Sabino‐Santos et al, ; Straková et al, ; Těšíková, Bryjová, Bryja, Lavrenchenko, & Goüy de Bellocq, ; Zhang, ). This new information opens the possibility to assess the role of North American shrews and bats as host of hantavirus species.…”
Section: Discussionmentioning
confidence: 99%
“…Until the decade of 2000, Hantaviridae family was restricted to Rodentia, (Padula et al, ; Schmaljohn & Hjelle, ; Torres‐Pérez et al, ); however, since the early 2000s, recent discoveries found some hantavirus species in Indian shrews [order: Soricomorpha] (Klempa et al, ; Zhang, ) and American and European bats (Sabino‐Santos et al, ; Straková et al, ; Těšíková, Bryjová, Bryja, Lavrenchenko, & Goüy de Bellocq, ; Zhang, ). This new information opens the possibility to assess the role of North American shrews and bats as host of hantavirus species.…”
Section: Discussionmentioning
confidence: 99%
“…Hantaviruses are predominantly rodent-borne pathogens and transmission to humans can lead to severe diseases and death. Species of hantaviruses have been identified in bats from Africa and Asia, expanding the potential reservoirs range and genetic diversity of these viruses [115][116][117][118][119][120]. Hantaan orthohantavirus (HTNV) was isolated from two broadly distributed insectivorous bat species (Eptesicus serotinus and Rhinolophus ferrumequinum) [117].…”
Section: Sequences Inmentioning
confidence: 99%
“…Evidence of a lethal genotype of Andes orthohantavirus (ANDV), Araraquara orthohantavirus (ARQV), has been documented among several Neotropical bats in Brazil [118,120]. ARQV is one of the most virulent and lethal among all hantaviruses in humans and viral RNA closely related to ARQV was detected in urine of the common vampire bat (Desmodus rotundus) [119]. These studies highlight that bats are probably playing an under appreciated part on the maintenance, circulation, and transmission of hantavirus in nature.…”
Section: Sequences Inmentioning
confidence: 99%
“…Therefore, we also tested samples of saliva from all captured bats and intestine from the tested bats, but, again, we failed to find any positive sample, even from those bats serologic positive. Although we have failed to detect viral RNA, our RT‐PCR approach is suitable to detect distinct hantaviruses that show high homology with South American hantaviruses (Moreli et al, ; Sabino‐Santos et al, ). Altogether, these results may also indicate that the studied bats can clear the infection, since no viral RNA could be detected.…”
Section: Resultsmentioning
confidence: 95%
“…Since N protein is conserved among hantaviruses, our ELISA approach, as previously described (Figueiredo et al, ), targets a conserved region throughout the entire clade of ANDV (Figueiredo et al, , ; Sabino‐Santos et al, ) and, therefore, can detect these distinct hantaviruses species and genotypes that cause disease among humans in Brazil. Evidence of a lethal genotype of ANDV, ARQV, has been documented among several Neotropical bats in Brazil and viral RNA closely related to ARQV was found in urine, heart and liver tissues of the common vampire bat Desmodus rotundus (haematophagous), blood of Carollia perspicillata (frugivorous) and D. rotundus , and in the lung and kidneys tissues of Diphylla eucadata (haematophagous) (de Araujo et al, ; Sabino‐Santos, ; Sabino‐Santos et al, ). This suggests that bats can probably shed hantavirus in their excreta while maintaining the infection in their organs.…”
Section: Resultsmentioning
confidence: 99%